The supply chain management of fishing industry in Rokan Hilir, Province of Riau, Indonesia / Eni Yulinda, Kamisah Supian and Mazni Saad - Yulinda, Eni; Supian, Kamisah; Saad, Mazni (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This survey research was conducted in Rokan Hilir regency, one of the largest fishing industry centers in Riau Province, Indonesia. There are two objectives of this research, namely to analyze descriptively the characteristics of fishing companies and implementation of supply chain management for the fishing industry. A total of 270 fishing companies, four collectors, and one fish exporter were taken as respondents. The results show that most of the fishing companies were small-scale businesses, with vessel sizes of 3-6 gross tonnage (62.60 percent); fishing gear size less than 3,000 square meters (84 percent); the number of crew/ fishermen 3-4 peoples (52 percent); and has a turnover of less than IDR 50 million per year (50.34percent). The entities involved in the supply chain for the fishing industry are fishermen who own fishing companies and Tauke (fish collectors, agents, exporters, and importers of fish). The smooth flow of goods (fish and others), the flow of money, and the flow of information between fishermen and Tauke is caused by the existence o f a patron-client relationship based on mutual trust. The smooth flow is also due to the existence of kinship relationship between the Tauke and the availability of supporting facilities for the fishing industry, such as ice factories, transportation facilities, banks, and means of communication (cellular phones and internet).